Unlocking the Hidden Potential of Rosemary (Salvia rosmarinus Spenn.): New Insights into Phenolics, Terpenes, and Antioxidants of Mediterranean Cultivars - Andrea Baptista; Felicia Menicucci; Cecilia Brunetti; Luana Beatriz dos Santos Nascimento; Dalila Pasquini; Francesca Alderotti; Cassandra Detti; Francesco Ferrini; Antonella Gori (Plants)
Rosemary (Salvia rosmarinus Spenn. syn. Rosmarinus officinalis L.) is a Mediterranean aromatic species used both as an official herb and as a spice. Different cultivars may exhibit diverse phytochemical compositions, making a comprehensive chemical characterization pivotal for a targeted selection of valuable cultivars. This study aimed to characterize and compare the phenolic and terpene composition and content of leaf extracts of six Mediterranean rosemary cultivars: ‘Alba’, ‘Arp’ ‘Ginger’, ‘Gorizia’, ‘Tuscan Blue’, and ‘Roseus’. HPLC-DAD analysis revealed a similar phenolic composition in all the cultivars, but quantitative differences were observed. The main compounds were carnosic acid derivatives, flavonoids (e.g., luteolin, apigenin, and quercetin glucosides), rosmarinic acid, caffeic acid, and other hydroxycinnamic acid derivatives. The highest phenolic content was found in ‘Alba’, with a predominance of carnosic acid derivatives, whereas the lowest was found in ‘Ginger’ and ‘Gorizia’. The GC-MS analysis evidenced quantitative differences among the cultivars. Particularly, ‘Alba’ contained the highest terpene content, whereas ‘Arp’ and ‘Gorizia’ showed the lowest values. Regarding the antioxidant activity, ‘Alba’ exhibited the highest values as regards phenols, while for terpenes, the highest ones were obtained for ‘Ginger’ and ‘Tuscan Blue’. Significant Pearson correlations were obtained between the total phenol/terpene content and the antioxidant activity. The chemical characterization of these cultivars provides relevant information to produce the rosemary phytocomplexes, finding multiple industrial applications.